2007
DOI: 10.1021/np068075p
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitane-Type Triterpenoids from the Fruits of Momordica charantia and Their Cancer Chemopreventive Effects

Abstract: Thirteen cucurbitane-type triterpene glycosides, including eight new compounds named charantosides I (6), II (7), III (10), IV (11), V (12), VI (13), VII (16), and VIII (17), and five known compounds, 8, 9, 14, 15, and 18, were isolated from a methanol extract of the fruits of Japanese Momordica charantia. The structures of the new compounds were determined on the basis of spectroscopic methods. On evaluation of these triterpene glycosides and five other cucurbitane-type triterpenes, 1-5, also isolated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 26 publications
5
109
0
1
Order By: Relevance
“…The combined EtOAc soluble layer was subjected to repeated silica gel column chromatography and further purification by semi-preparative HPLC to yield compounds 1-9. The eight known compounds (2)(3)(4)(5)(6)(7)(8)(9) were identified by comparing their physical and spectral data with the reported values. The structure of the new sterol (1) was elucidated as follows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined EtOAc soluble layer was subjected to repeated silica gel column chromatography and further purification by semi-preparative HPLC to yield compounds 1-9. The eight known compounds (2)(3)(4)(5)(6)(7)(8)(9) were identified by comparing their physical and spectral data with the reported values. The structure of the new sterol (1) was elucidated as follows.…”
Section: Resultsmentioning
confidence: 99%
“…Previous pharmacological studies have showed that the extracts or compounds of tissues of M. charantia possess anti-diabetic and anti-inflammatory activities. [1][2][3] Chemical investigations of M. charantia also revealed that more than seventy cucurbitane-type triterpenes have been isolated form the fruits, [3][4][5][6][7][8][9][10][11][12] seeds, 13,14 root, 15 and leaves and vines 16,17 of M. charantia. As part of our program aimed at the discovery of bioactive secondary metabolites from Taiwanese M. charantia, we had reported the isolation and structure elucidation of twenty-five cucurbitane-type triterpenoids from the MeOH extract of the stems of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the concentration of α-ESA needed for inhibition was considerably lower than that of CLA. Previous studies found that bitter melon seed or fruit extracts were capable of anticancer activity in a rat colonic aberrant crypt foci model (18), a mouse skin carcinogenesis model (19), a DLD-1 (colorectal adenocarcinoma) mouse xenograft model (10), and a mouse mammary tumor model (6). Therefore, although a number of studies have suggested that various bitter melon components/extracts have anticancer activity, no prior work has evaluated the specific effects of α-ESA in relation to breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The cucurbitane-type triterpenoids and their aglycones have shown some biological effects beneficial in treating diabetes and obesity, and possess anticancer, anti-HIV and antifeedant properties [7,39]. More than fifty cucurbitacins and cucurbitane glycosides from the fruits, seeds, leaves, vines and stems have been reported [40][41][42][43][44][45][46][47][48]. Recently, Chen et al (2008) isolated and structured elucidation of nineteen cucurbitacins named kuguacins A-E from the roots of MC [49] and kuguacins F-S [50] from the vines and leaves of MC.…”
Section: Phytochemicals and Cucurbitane Triterpenoidsmentioning
confidence: 99%
“…Recent studies further indicate that the chemical modification and reduction of ribosome-inactivating protein in BME, significantly reduced its in vivo immunogenicity, but retained its antiproliferative activity as measured by DNA fragmentation and caspase-3 activation [100]. Cucurbitane-type triterpenoids, charantosides, from a methanol extract of the fruits of MC also inhibited mouse skin carcinogenesis induced by 7,12-dimethylbenz[a]anthracene (DMBA) or peroxynitrite plus 12-O-tetradecanoylphorbol-13-acetate (TPA) [45] α-ESA in bitter melon seed oil suppressing the growth of DLD-1 human colon cancer cells by apoptosis induction via lipid peroxidation [101]. α-ESA, which is converted to conjugated linoleic acid in vivo, had a stronger suppressive effect than the conjugated linoleic acid on tumor cell growth.…”
Section: Anticancer In Vivo Studiesmentioning
confidence: 99%